Spreading sequences for asynchronous MC-CDMA revisited accurate bit error rate analysis. - Qinghua Shi (IEEE Transactions on communications)
The bit error rate (BER) of an asynchronous multicarrier code-division multiple-access system in an additive white Gaussian noise channel is evaluated using Monte Carlo integration and moment-generating function methods. The BER performance for different families of spreading sequences is investigated. Numerical results show that the approach of a recently published paper (see Popovic, B.M., IEEE Trans. Common., vol.47, p.918-26, 1999) cannot give an accurate BER because the interference from other subcarriers has been omitted. Some new findings about the performance of different sequences are also presented.